2021
DOI: 10.1021/acs.organomet.1c00182
|View full text |Cite
|
Sign up to set email alerts
|

Hypercrosslinked Polymer Platform-Anchored Single-Site Heterogeneous Pd–NHC Catalysts for Diverse C–H Functionalization

Abstract: We demonstrate a new class of hypercrosslinked polymer (HCP) platform-anchored single-site heterogenized Pd–NHC catalysts for multipurpose C–H functionalization reactions. This new class is represented by a set of three catalysts, viz., HCP-B- Me NHC-Pd, HCP-B- Bn NHC-Pd, and HCP-TPM- Me NHC-Pd, having a variation on the structural feature of the anchoring polymeric platform. All three catalysts were fully characterized via diverse solid-state characterization and analytical techniques such as X-ray phot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 49 publications
0
17
0
Order By: Relevance
“…(K) N,N′-dimethyl-benzimidazolium iodide and triphenylmethane-based HCP catalyst with Pd as the active site . (L) Several examples of halogenation reactions promoted by a catalyst developed by Mandal et al, including yields. Reprinted with permission from ref .…”
Section: Wide Range Of Applications For Hyper-cross-linked Polymersmentioning
confidence: 99%
See 3 more Smart Citations
“…(K) N,N′-dimethyl-benzimidazolium iodide and triphenylmethane-based HCP catalyst with Pd as the active site . (L) Several examples of halogenation reactions promoted by a catalyst developed by Mandal et al, including yields. Reprinted with permission from ref .…”
Section: Wide Range Of Applications For Hyper-cross-linked Polymersmentioning
confidence: 99%
“…(L) Several examples of halogenation reactions promoted by a catalyst developed by Mandal et al, including yields. Reprinted with permission from ref . Copyright 2021, American Chemical Society.…”
Section: Wide Range Of Applications For Hyper-cross-linked Polymersmentioning
confidence: 99%
See 2 more Smart Citations
“…HCPs exhibit a permanent porosity and high surface area, and their synthesis is straightforward, requiring only common Lewis acid catalysts to initiate polymerization, such as Fe­(III) chloride and Al­(III) chloride, or organic Brønsted acids. , This simplicity and potential for scale-up explain the scientific interest around these materials. In fact, some HCPs are already commercially available (e.g., ion-exchange polymeric resins) while others are being developed and tailored for different applications related to gas separation/storage, liquid phase adsorption, , and catalytic organic transformations. In particular, HCPs have recently been investigated for CO 2 capture ,, and CO 2 photoconversion to value-added chemicals. , Martin et al reported a biphenyl–xylene HCP with CO 2 uptake capacity of 1.7 and 13.4 mmol g –1 under atmospheric pressure and 30 bar, respectively, exceeding that of commercial adsorbents like zeolite 13X and activated carbons BPL and Norit R under similar conditions . Su et al studied an amine-functionalized HCP that displayed selective CO 2 uptake over N 2 , a feature they attributed to the high density of primary amines and the relatively small pore size of the material .…”
Section: Introductionmentioning
confidence: 99%